ISLAMIC MODERATION MODEL IN MANAGING MOSQUE TO INCREASE PHILANTHROPY FUND AT JOGOKARIYAN MOSQUE YOGYAKARTA - Ahmad Mifdlol Muthohar (Pascasarjana IAIN Metro, 2019)
The purpose of this study is to find out Islamic moderation model which is successfully developed by Jogokariyan mosque. The research method used in this study is a qualitative method with descriptive analysis. The research findings show that Islamic moderation approach in managing a mosque gives optimal effect on collecting philanthropy fund. Islamic moderation model developed by Jogokariyan Mosque has characteristics: 1) the leader of the mosque is also the leader of community; 2) Mosque belongs to community and everyone is allowed to use the facilities; 3) philanthropy fund is used not only for ritual aspect but also for social and economic empowerment of community; 4) involving the elements and roles of community to build sense of belonging toward the mosque; 5) developing the icon of Java community such as prayer cap as important icon of the mosque and as the typical merchant to foster economy.